3D-printed cuvette holder clip for a spectrophotometer - Warangkana Yimkosol; Nungnit Wattanavichean; Manchuta Dangkulwanich (BMC Research Notes)
Abstract Objective Instrument downtime hinders the productivity of research and teaching activities within institutions. The ability to promptly repair malfunctioning instruments is therefore essential. This work reports the successful design and fabrication of a small but essential part of a spectrophotometer: the cuvette holder clip. This clip is not available for individual purchase from the manufacturer. Results The designed 3D-printed replacement clip effectively secured the cuvette in its holder, restoring stable and reproducible absorbance measurements. The material costs is less than 1 USD cent. The 3D model presented in this work provides a rapid and affordable repair to a spectrophotometer commonly used in teaching laboratories and can be modified for a similar repair of other instruments.